2023
DOI: 10.1021/acs.chemmater.3c00358
|View full text |Cite
|
Sign up to set email alerts
|

Planar Positive–Zero–Negative Thermal Expansion Transition in Crystalline Supramolecular Rotors

Abstract: Zero thermal expansion materials are crucial for manufacturing high-precision devices, but most of these materials discovered so far are inorganic. Organic zero thermal expansion materials are rare due to the need for precise control over the complex supramolecular interactions between organic groups in order to modulate their thermal expansion properties. Here, we report a novel organic crystalline supramolecular rotor, [(3-chloro-1-adamantylammonium)(18-crown-6)]ClO4, which exhibits planar positive–zero–nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…ZTE behavior in organic molecular materials is seldom due to the difficulty in controlling the ubiquitous complex supramolecular interactions. 30 Recently, we have reported a near ZTE characteristic along with anisotropic NTE and PTE characteristics in an imidazole-based single-component system. 12 Very recently, Nakamura et al have reported planar PTE-ZTE-NTE characteristics with reasonable CTEs in an 18crown-6 complex-based metal-free crystalline supramolecular rotor.…”
Section: ■ Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…ZTE behavior in organic molecular materials is seldom due to the difficulty in controlling the ubiquitous complex supramolecular interactions. 30 Recently, we have reported a near ZTE characteristic along with anisotropic NTE and PTE characteristics in an imidazole-based single-component system. 12 Very recently, Nakamura et al have reported planar PTE-ZTE-NTE characteristics with reasonable CTEs in an 18crown-6 complex-based metal-free crystalline supramolecular rotor.…”
Section: ■ Introductionmentioning
confidence: 94%
“…A very few cases of single-component organic materials with colossal PTE and NTE effects, i.e., coefficient of thermal expansion, CTE > ± 100 × 10 –6 K –1 , are reported in the literature. ,, Various inorganic systems such as oxides ,,,, and metal cyanide, , coordination polymers, , and metal–organic frameworks ,,, are known to exhibit NTE and ZTE characteristics. ZTE behavior in organic molecular materials is seldom due to the difficulty in controlling the ubiquitous complex supramolecular interactions . Recently, we have reported a near ZTE characteristic along with anisotropic NTE and PTE characteristics in an imidazole-based single-component system .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 However, organic molecular crystals that switch from NTE to PTE or vice versa without a thermal phase transition have only rarely been reported. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Among various types of supramolecular rotors, crown-ether-based rotors are of particular interest, which have been intensively studied from time to time. 29–40 In confined space, the conformationally flexible crown ethers are capable of forming stable supramolecular complexes with primary ammonium (R-NH 3 ) + ions through multiple O⋯H–N hydrogen bonds, which bind and/or semi-encapsulate the primary ammonium ions, providing a confined environment for their rotation. Following this strategy, a series of crown-ether-based supramolecular rotors had been prepared merely by a one pot self-assembly method, without intricate chemical processes.…”
Section: Introductionmentioning
confidence: 99%